2019
DOI: 10.1177/1129729819874312
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of successful arteriovenous fistulae creation including intraoperative transit time flow measurement

Abstract: Background: The prevalence of hemodialysis patients is increasing, and it is important to create the arteriovenous fistula as early as possible to avoid hemodialysis by central venous catheter. International guidelines recommend arteriovenous fistula as the vascular access of first choice. Arteriovenous fistulae are associated with a failure rate of 23%. The success of an arteriovenous fistula can be evaluated intraoperatively by physical examination and by measuring the blood flow. Objectives: The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…25,27 Multiple risk factors affect AVF maturation, including gender, age, target vein size, target arterial size, diabetes, peripheral arterial disease, [28][29][30] and surgeons' characteristics and experience. 31 Careful site selection, 32 pre-operative ultrasound assessment of vessels, [33][34][35] intra-operative flow measurement, 36 ultrasound-guided cannulation in early matured SCVA, 37,38 and SCVA maturation tracking system 39 are some of the ways to enhance SCVA usage and shorten CVC-dependent time and reduce healthcare expenditure. Appropriate use of AVG in patients with unfavorable venous asset might also minimize the percentage of failure-to-mature AVFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,27 Multiple risk factors affect AVF maturation, including gender, age, target vein size, target arterial size, diabetes, peripheral arterial disease, [28][29][30] and surgeons' characteristics and experience. 31 Careful site selection, 32 pre-operative ultrasound assessment of vessels, [33][34][35] intra-operative flow measurement, 36 ultrasound-guided cannulation in early matured SCVA, 37,38 and SCVA maturation tracking system 39 are some of the ways to enhance SCVA usage and shorten CVC-dependent time and reduce healthcare expenditure. Appropriate use of AVG in patients with unfavorable venous asset might also minimize the percentage of failure-to-mature AVFs.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Effective training of access surgeons on clinical decision-making and skill should be a focus of the specialty. 36,43 More effort should be injected into the healthcare system to monitor and enhance a high SCVA success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative TTF is commonly used in coronary artery bypass surgery to assess graft flow and has been found to show significant correlations with graft patency in both short-term and mid-term evaluations [8]. However, few studies have applied intraoperative TTF to analyze AVF creation [9]. Our study found that TTF was a predictor of RCAVF maturation (p<0.001) and identified a TTF of ≥105 mL/min as the most suitable cutoff value (AUC, 0.71).…”
Section: Discussionmentioning
confidence: 99%